Sustainability, the Circular Economy, and Digitalization in Libyan Organizations - Mohammed, Najat (Journal of Environmental Economics and Sustainability, 2025)
An economic system that eliminates material and energy loops in systems of   production and consumption is known as the circular economy (CE). In this regard, digital technologies (DT) are viewed as answers for the implementation of the Circular Economy. Even though digital technologies are being used more and more in industry, little is known about how they specifically affect the circular economy. Therefore, the purpose of this study is to determine whether and how a limited number of organizations are utilizing digital technologies to support their circular economy and sustainability goals. inductive research approach, which using questionnaires to gather data from IT directors, senior IT professionals, or organization managers in a variety of organizations. The article concluded that where organisations in Libya  rely significantly on sustainability initiatives and the objectives of the circular economy, the relation with digital technology deployment is not clear. Digital technologies such as Internet of Things , social media ,  analytics & big data, and Mobile computing are played a crucial role in supporting sustainability and the circular economy within organizations.